1985
DOI: 10.1002/jmv.1890160402
|View full text |Cite
|
Sign up to set email alerts
|

Inadequacy of lmmunoglobulin M hepatitis B core antibody in detecting acute hepatitis B virus infection in infants of HBsAg carrier mothers

Abstract: To study the usefulness of IgM hepatitis B core antibody (anti-HBc IgM) for detecting hepatitis B virus infections in infants of hepatitis B surface antigen (HBsAg) carrier mothers, serial serum samples from 86 infants of carrier mothers were tested for anti-HBc IgM with a highly specific enzyme immunoassay. Asymptomatic hepatitis B infection occurred frequently in infants under 12 mo of age. Anti-HBc IgM never became positive in 25 infants infected under 9 mo old. It was positive in only 1 of 6 infected at 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The HBcAg efficiently activate antigen‐presenting cells, especially naive B cells, leading to generation of T‐helper 1 (Th1) dominant immunity and triggering the humoral immune response for the production of IgM and IgG anti‐HBc 30 . In keeping with clinical observations, IgM anti‐HBc is rarely detected in infants who contracted the infection from their HBV carrier mothers, nor in immunodeficient adults with acute HBV infection 9,31 . These lines of evidence indicate that IgM anti‐HBc may reflect the cytoplasmic expression of HBcAg in the liver cells, which leads to active liver disease.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The HBcAg efficiently activate antigen‐presenting cells, especially naive B cells, leading to generation of T‐helper 1 (Th1) dominant immunity and triggering the humoral immune response for the production of IgM and IgG anti‐HBc 30 . In keeping with clinical observations, IgM anti‐HBc is rarely detected in infants who contracted the infection from their HBV carrier mothers, nor in immunodeficient adults with acute HBV infection 9,31 . These lines of evidence indicate that IgM anti‐HBc may reflect the cytoplasmic expression of HBcAg in the liver cells, which leads to active liver disease.…”
Section: Discussionmentioning
confidence: 82%
“…30 In keeping with clinical observations, IgM anti-HBc is rarely detected in infants who contracted the infection from their HBV carrier mothers, nor in immunodeficient adults with acute HBV infection. 9,31 These lines of evidence indicate that IgM anti-HBc may reflect the cytoplasmic expression of HBcAg in the liver cells, which leads to active liver disease. In the present study, although the serum ALT level of patients with CHB with acute flare who had index values ≤ 1.2 was comparable with that of those with index values > 1.2, the peak level of ALT as well as the index values of IgM anti-HBc were significantly higher in patients with AHB than those with acute flare of CHB.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Senegal has shown HBs and/or HBe antigenemia at birth, but at the time authors considered the absence of IgM anti-HBc in newborn sera an argument for exposure to maternal blood at delivery, rather than active in utero infection (14). However, further studies using subjects with proven perinatal HBV infection in Asia have shown that newborns as well as 9-month-old infants do not develop IgM anti-HBc (6,26). Also in our study, all infants tested at birth or at 6-7 months were IgM anti-HBc negative, despite evidence of some transitional HBV infection.…”
Section: Discussionmentioning
confidence: 96%
“…o-' = 1-0. [14,48,49,75,77], 2 from Hong Kong [66,78], and 1 each from Japan [76] and Thailand [68]. Developed includes 4 surveys from India [69,70,79,80], and 1 each from Egypt [71], and Kuwait [73].…”
Section: Modelling Hbv Infection Patternsmentioning
confidence: 99%